Stress Uniformity Analyses on Nonparallel End-Surface Rock Specimen during Loading Process in SHPB Tests. (11th July 2018) - Yuan, Pu; Ma, Qin-yong; Ma, Dong-dong
Abstract : To investigate the influence of nonparallel end-surface on stress uniformity during loading process in rock SHPB test, SHPB numerical simulations have been carried out by LS-DYNA when end-face nonparallelism is within 0.40% and Young's modulus ranges from 14 GPa to 42 GPa. Isotropic linear elastic model is applied for elastic steel pressure bar, and HJC constitutive model is chosen for rock specimen. Numerical simulation results indicate that fluctuation effect exists in both reflected stress waves and transmitted stress waves, and it is enhanced with the increase of end-surface nonparallelism. The stress nonuniformity coefficient attenuates in a serrated fluctuation. With the increase of end-surface nonparallelism, the amplitude of transmitted stress wave gradually reduces, while stress nonuniformity coefficient increases. Stress equilibrium time first decreases slightly then increases in a step type. Therefore, nonparallel end-surface leads to two reverse results for stress uniformity during SHPB loading process, extending stress equilibrium time and shortening stress equilibrium time. And the influence on shortening stress equilibrium time is weak, while the influence on extending stress equilibrium time is great. When end-surface nonparallelism is 0.10%, stress equilibrium time achieves its lowest value whatever Young's modulus is. Hence, end-surface nonparallelism of the rock specimen is suggested to be controlled within 0.10% when conducting SHPB tests.